Z historii zmagań wywiadów Polski i Niemiec w latach 1920-1939. Radca kryminalny Oskar Reile kontra mjr Jan Henryk Żychoń (Kronika Bydgoska, 2020)
Polish and German intelligence services’ struggled in a borderland war. The Nazis, after they seized Poland in September 1939, due to thoughtlessness of Polish archivists of the 0nd Division of the General Staff of the Polish Army, found in the Legion Fort in Warsaw a number of original classified documents, including the Bydgoszcz files of the 3rd Branch of the 0nd Division. They tried about a hundred former Polish agents in the People’s Court of Nazi Germany. The mentioned article describes the trial of agent Czesława Irena Bociańska. She was sentenced to ten years in prison. Her partner, Col. Mieczysław Pożerski detained without sentence in the Dachau concentration camp, where he died in 1941.